Bioapplications of Polythiophene‐g‐Polyphenylalanine‐Covered Surfaces. Issue 18 (19th August 2015) - Guler, Emine; Akbulut, Huseyin; Bozokalfa, Guliz; Demir, Bilal; Eyrilmez, Gizem Oyman; Yavuz, Murat; Demirkol, Dilek Odaci; Coskunol, Hakan; Endo, Takeshi; Yamada, Shuhei; Timur, Suna; Yagci, Yusuf
<x xml:space="preserve">Abstract</x> The fabrication of electro and bioactive surfaces by electrochemical deposition of the thiophene‐functionalized polyphenylalanine macromonomer (T‐g‐PPhe) is reported. The resulting conducting graft copolymer, polythiophene‐graft‐polyphenylalanine (PT‐g‐PPhe) formed on the indium tin oxide (ITO) glass surface, is characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, and fluorescence microscopy. Then, possible uses of PT‐g‐PPhe as matrices in the sensor design for both electrochemical biosensing and cell adhesion studies are investigated. In the first part, PT‐g‐PPhe that is deposited on ITO is further functionalized with the arginylglycylaspartic acid peptide via 1‐Ethyl‐3‐(3 dimethylaminopropyl) carbodiimide for the selective cell adhesion. Immunofluorescence staining is performed to detect the difference between adherences of "integrin αvβ3" receptor positive (U87‐MG) and negative (HaCaT) cell lines on to the biofunctional surface. In the second part, an electrochemical glucose sensor is constructed by immobilizing glucose oxidase on the surface of PT‐g‐PPhe, which is deposited on a glassy carbon electrode.